2012
DOI: 10.1016/j.neuropharm.2012.04.018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pregabalin on sensorimotor gating in ‘low’ gating humans and mice

Abstract: Pregabalin, an anticonvulsant and anxiolytic compound that binds to α2-δ auxiliary subunit Types 1 and 2 of voltage-gated calcium channels, has been shown to reduce excitatory neurotransmission partially through modulation of glutamatergic signaling. Prepulse inhibition (PPI) of startle is an operational measure of sensorimotor gating impacted by disruption of the glutamatergic system and is reduced in schizophrenia patients. Dysregulation of the glutamatergic system has also been implicated in the pathophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 61 publications
(82 reference statements)
1
7
0
Order By: Relevance
“…Eyeblink data were scored via SR-HLAB EMG Utilities software as previously described (Acheson et al, 2012a,b). In brief, eyeblink responses were examined on a trial by trial basis at a window starting 100 ms before the startle pulse and ending 200 ms after the pulse.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eyeblink data were scored via SR-HLAB EMG Utilities software as previously described (Acheson et al, 2012a,b). In brief, eyeblink responses were examined on a trial by trial basis at a window starting 100 ms before the startle pulse and ending 200 ms after the pulse.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in high trait anxious participants or other anxiety disorders are inconsistent, showing either normal or reduced fear inhibition as measured by safety signal learning (Kindt and Soeter, 2014; Gazendam et al, 2013; Lissek et al, 2009). Reduced inhibition in PTSD patients is thought to reflect disruption of frontal cortical and hippocampal circuits to inhibit amygdala activation and concomitant fear responses (Admon et al, 2013; Acheson et al, 2012a,b). However, increased fear responding to conditioned cues, aversive contexts, or over-generalization of fear responses are shown across multiple anxiety disorders and thus may reflect biological processes that are shared across disorders (McTeague and Lang, 2012; Lissek et al, 2013; Grillon et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Sound levels were measured using continuous tones calibrated using a Quest Sound Level Meter on the A scale, coupled to the headphones by an artificial ear. EMG responses were recorded using the SDI SR-HLAB EMG system coupled with a Dell desktop computer as previously described (Acheson et al 2012). Gain was adjusted to 0.5 (0.5 mV electrode input amplified to 2500 mV signal output) and band pass filtered (100–1000 Hz).…”
Section: Methodsmentioning
confidence: 99%
“…This may reflect the fact that, at baseline, mechanisms for sensorimotor gating function at their optimal levels; additionally, experimental stimulus parameters (in particular, prepulse intervals) are typically selected to maximize inhibitory effects of prepulses and thereby are most sensitive for detecting drug-induced reductions in inhibition. However, strains of both mice and rats have been identified with relatively low basal PPI levels, and investigators have also taken the strategy of identifying "low gating" rats within a particular strain, and in both cases, these strains and substrains have been shown to be more sensitive to PPI-enhancing effects of drugs or brain stimulation (Acheson et al 2012;Angelov et al 2014;Swerdlow et al 2006). Roussos et al (2008) reported parallel findings in humans, in which healthy subjects homozygous for the Val allele of the rs4680 COMT polymorphism exhibited low basal PPI levels and PPI-enhancing effects of the COMT inhibitor, tolcapone, while individuals homozygous for the MET allele of rs4680 exhibited high basal PPI and PPI-reducing effects of tolcapone.…”
Section: Drug-enhanced Ppi As a Biomarker For Pact?mentioning
confidence: 99%